Dental-Implant Retained Mandibular Overdenture: A Case Report - Gupta, Rahul; Singh, Raj Kumar; Basnet, Bishal Babu (Birat Journal of Health Sciences, 2018)
The prosthetic management of the patient with resorbed ridge has long been a major challenge for dentistry. Conventional complete denture for long was the standard of care for all such patients. However, most patients find it difficult to adapt to mandibular denture due to lack of retention and stability. Recent scientific studies carried out over the past decade have determined that the benefits of a mandibular two-implant overdenture are sufficient to propose the two-implant overdenture-rather than the conventional denture - as the first treatment option. BJHS 2018;3(2)6:488-491.